Humanizing strategy : how to master emotions, values and beliefs when you execute plans - Verwaeren, Geert, ....- (Tielt : LannooCampus, 2021)
Based on more than 25 years of experience - Unique perspective that emphasizes values, beliefs and emotions - Unconventional approach Strategy execution is complex. Three out of four organizations fail to implement their strategies, despite consultancies, literature on the subject and all available best practices. But why exactly do most strategies fail? Based on leading research, real stories, case studies and practical tools, the author takes you into the world of values, beliefs, emotions and often hidden underlying motivational forces that influence individual and collective behavior in organizations. He shows how consciously and effectively dealing with these human dynamics, often neglected in the strategic process, has a major influence on the performance of your organization and the successful realization of your strategy. If you are serious about making your strategy a success, have the urge to keep asking "why", and have the courage to take a less conventional approach, this book will inspire you.
Keywords: Organisaties ; strategie; Organizations ; people management; Organizations; strategy; Strategisch management